Examining patterns of injury occurrence in rural and urban settings in sub-Saharan Africa: A critical review of the literature - Buor, Daniel (Advances in Social Sciences Research Journal, 2018)
The paper critically reviews literature on patterns of injury occurrence in rural and urban areas in sub-Saharan Africa. Findings are based on research reports from eight countries purposively selected from major geographical regions in sub-Saharan Africa. From West Africa are selected Nigeria and Ghana; Uganda, Kenya and Tanzania represent East Africa; Rwanda for Central-Eastern Africa; Republic of South Africa for South Africa and Zambia for Central-South Africa. The selected countries are among those where adequate research work on injuries in urban and rural settings has been done. The Sahel region is not listed because it was found that no serious work on injury occurrence by rural and urban has been done in the region. Eight variables, namely, general causes of injury, rate of injury occurrence, severity of injury, persons involved in road traffic injuries (passengers and pedestrians), causes common to both settings, vehicles mostly involved in the injuries, child injuries and age group mostly affected form the basis for the analyses. The review establishes, among other patterns, that rural settings suffer greater severity and higher mortality from injuries through road traffic accidents and occupational (agricultural-related) injuries whilst other injuries including those suffered through pedestrian crossings, burns, cuts and falls are predominant in urban areas. Although a few works tilted the severity of the injuries through motor traffic accidents to the urban areas, the high incidence of occurrence in both rural and urban areas was still upheld. It is recommended, among other considerations, that rural areas be given priority in the establishment of injury clinics whilst the spatial techniques of remote sensing and geographical information systems (GIS), the mixed methods approach and use of inferential statistics be more applicable to capturing and analysing data on injuries.